An Interpersonal Dialogue Group for Students With and Without Disabilities. Issue 3 (3rd July 2017) - Lee, Cheryl D.
ABSTRACT: This narrative documents my experience cofacilitating a group of 17 undergraduate students. One half of the students and the cofacilitator of the group had disabilities. The purpose was to foster understanding between students with disabilities and students who were able bodied. The group members learned about people with diverse disabilities and the discrimination and difficulties they experienced. Students with disabilities learned about perceptions of the students who were able bodied and their differences and commonalities. Group members experienced mutual aid. The author learned important lessons about herself as a group worker and social work educator.